2010
DOI: 10.1007/s13258-010-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of STRA8 as a transcriptional factor

Abstract: The Stra8 gene is a retinoic acid responsive gene. Its expression in premeiotic germ cells in both sexes implies that STRA8 protein plays roles for the progression of meiosis. Stra8 deficient germ cells do not initiate meiotic chromosome condensation and DNA double strand breaks. Its deficient mice were infertile. STRA8 is required for the transition into meiosis in both female and male germ cells. In addition its expression was confirmed in trophoblast giant cells in placenta, indicating another physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…However, when the plasmid was transfected into pig SSCs, fluorescence was observed in the cytoplasm as well as the nucleus. Stra8 has previously been found in the nucleus in P19 cells and F9 cells [33]. In this study, we found pig Stra8 has a HLH structure based on sequence analyses and is located in the nucleus of some SSCs.…”
Section: Resultssupporting
confidence: 60%
“…However, when the plasmid was transfected into pig SSCs, fluorescence was observed in the cytoplasm as well as the nucleus. Stra8 has previously been found in the nucleus in P19 cells and F9 cells [33]. In this study, we found pig Stra8 has a HLH structure based on sequence analyses and is located in the nucleus of some SSCs.…”
Section: Resultssupporting
confidence: 60%
“…Here, we also found this distinct intracellular localization and the dynamic changes of these two compartments with prolonged RA induction, but the functions of cytoplasmic and nuclear STRA8 were unknown. Previous studies demonstrated that STRA8 directly binds to DNA and possesses transcriptional activity4849. By using a yeast two-hybrid system, Zheng et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Choi et al . ), although the functions of STRA8 have not been scrutinized and remain controversial.…”
Section: Retinoic Acid‐stra8 Signaling Cascade For Meiosismentioning
confidence: 99%
“…Interestingly, a recent report has demonstrated that periodic RA-Stra8 signaling is also involved in facilitating differentiation of spermatogonial stem cells (Endo et al 2015). Mechanistically, some reports show that STRA8 protein resides in both cytoplasm and nucleus and that nuclear STRA8 may function as a transcription factor (Tedesco et al 2009;Choi et al 2010), although the functions of STRA8 have not been scrutinized and remain controversial.…”
Section: Retinoic Acid-stra8 Signaling Cascade For Meiosismentioning
confidence: 99%